Penilaian Konsumen Tentang Ekuitas Merek Shopping Mall di Surabaya (Studi Pada Tunjungan Plaza, Surabaya Plaza, dan Mal Galaxy) - Achmad Rofian Djunaedi; Sri Setyo Iriani (BISMA (Bisnis dan Manajemen), 2018)
Tunjungan Plaza, Surabaya Plaza, Mal Galaxy is part of a shopping mall that has a longevity brand in Surabaya, was established before the 2000th and still exist today. Tunjungan Plaza, Surabaya Plaza, and the Mal Galaxy have the outlet mall and tenant with famous brand, both brands from Indonesia and an international brand. Each of the shopping mall has a marketing strategy to build strong brand equity at the consumers perception. Brand equity may increase or decrease the value given by the shopping mall to the company or its customers. This research aims to determine consumers assessment of shopping mall brand equity in Surabaya, brand equity is measured by brand awareness, brand association, perceived quality, and brand loyalty. These results shows that Tunjungan Plaza is a shopping mall that brand awareness is remembered by most responden, most positively associated, and the highest brand loyalty, while the Mal Galaxy  is a shopping mall which considered by respondents to the best perceived quality. Overall, Tunjungan Plaza is a shopping mall which has the strongest brand equity in Surabaya.